Evaluation of Knowledge Levels, Attitudes and Influencing Factors of Physicians Working in Secondary Health Care Services in One Province, about Communicable Diseases Notification (Turkey Health Literacy Journal, 2023)
Abstract Surveillance of communicable diseases is the regular and continuous collection, analysis, interpretation and feedback of data for the prevention and control of diseases. The first step is the collection of data, and done through the notification system created in line with the needs of the country. The aim of our research is to determine the knowledge and attitudes of physicians on notification system. Mean age is 40.9+9.0 years, 42.3% of them received training on notification system, and 52.7% of 353 physicians stated that they did not report any communicable diseases. Among the reasons for not reporting are not knowing that they should make a notification and how to make a notification and not having time. 69.8% of those who reported and 47.3% of those who did not, received training. Reporting was found to be 2.6 times (95% CI: 1.5-4.3%) among those who received training. The mean knowledge score is 11.0+7.9. Physicians’ reporting and their level of knowledge about the notification system are related to receiving a training. Regular and continuous training will help increase the level of timely and complete reporting of diseases by physicians.